Daily runoff and its potential error sources reconstructed using individual satellite hydrological variables at the basin upstream - Fok, Hok Sum; Chen, Yutong; Zhou, Linghao (Frontiers in Earth Science, 2022)
Basin-scale hydropower operation and water resources allocation relies on in situ river discharge measured at a river mouth, which is referred to as runoff. Due to labor intensiveness and tight financial constraint, satellite hydrological variables have been advocated for reconstructing monthly runoff via regressing with nearby measured monthly river discharge over the past two decades. Nevertheless, daily runoff reconstruction by regressing with upstream satellite hydrological variables on a daily scale has yet to be examined. Data standardization approach is proposed for daily runoff reconstructed using satellite hydrological data at the upstream of Mekong basin. It was found that the accuracy of reconstructed and predicted daily runoff against in situ runoff were substantially increased, in particular the troughs (peaks) during dry (wet) seasons, respectively, when compared to that of the direct linear regression. The backwater impact on the runoff accuracy is negligible after standardization, implying the possibility for choosing the basin exit at the entrance of the river delta. Results generated from NN-based models do not improve consistently or even worse than that of the linear regression. The best forecasted runoff, yielding the lowest relative error of 0.086, was obtained from the upstream standardized water storage index. Further improvement lies in the methodology for mitigating the influence due to climate variability and extreme events.